2021
DOI: 10.1186/s40352-021-00144-8
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of victimization to violence among incarcerated women

Abstract: Introduction Limited research has focused on the trajectories of victimization to violence in women’s lives. Furthermore, literature assessing women’s use of violence has primarily focused on adult risk factors (e.g., substance use and criminal histories). Drawing from the pathway’s framework, we explored the impact of multiple forms of childhood victimization and subsequent harmful behaviors on adult-perpetrated violence among women convicted of violent or serious crimes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 79 publications
1
14
0
3
Order By: Relevance
“…Similarly, the study found that perpetration of violence by the women was mediated by victimization by those around them, with the target of the violence was similar to the type of victimization the participant had endured previously. Saxena and Messina (2021) conducted a study utilizing more than one thousand incarcerated women and found a strong trajectory between ACEs experienced and violent behavior, with those experiencing more ACEs being at a higher likelihood of engaging in violent behavior toward others. The researchers also found that initial arrest prior to the age of 18 and polysubstance use similarly increased the risk of women engaging in violence, which is consistent with previous research that has found that earlier criminal involvement and substance use are strongly positively correlated with ACEs (Fazel et al, 2006;Grella et al, 2013;Messina & Grella, 2006;Poister Tusher & Cook, 2010;Saxena et al, 2016;Tripodi & Pettus-Davis, 2013).…”
Section: Criminal Justice Researchmentioning
confidence: 99%
“…Similarly, the study found that perpetration of violence by the women was mediated by victimization by those around them, with the target of the violence was similar to the type of victimization the participant had endured previously. Saxena and Messina (2021) conducted a study utilizing more than one thousand incarcerated women and found a strong trajectory between ACEs experienced and violent behavior, with those experiencing more ACEs being at a higher likelihood of engaging in violent behavior toward others. The researchers also found that initial arrest prior to the age of 18 and polysubstance use similarly increased the risk of women engaging in violence, which is consistent with previous research that has found that earlier criminal involvement and substance use are strongly positively correlated with ACEs (Fazel et al, 2006;Grella et al, 2013;Messina & Grella, 2006;Poister Tusher & Cook, 2010;Saxena et al, 2016;Tripodi & Pettus-Davis, 2013).…”
Section: Criminal Justice Researchmentioning
confidence: 99%
“…Precisamente, diversas investigaciones en el campo de la criminología feminista han puesto de manifiesto que una de las características más comunes de estas mujeres es la "vulnerabilidad relacional" y la falta de relaciones de empatía y respeto mutuo en sus vidas (Chesney-Lind & Shelden, 2014;Nuytiens & Christiaens, 2015). El maltrato físico, sexual y emocional son frecuentes en sus relaciones de pareja (Belknap & Holsinger, 2006;Broidy et al, 2018;Owen et al, 2017;Saxena & Messina, 2021), y suelen venir acompañados de dependencia emocional y económica, así como del deterioro de sus redes sociales (Nuytiens & Christiaens, 2015;Van Voorhis et al, 2010).…”
Section: Conclusionesunclassified
“…Con todo, esperamos que este estudio contribuya al avance en esta línea de investigación, visibilizando la situación de las mujeres privadas de libertad y evidenciando sus necesidades, que requieren de intervenciones específicas, especialmente en el ámbito del trauma y la victimización (Saxena & Messina, 2021;Wright et al, 2012).…”
Section: Conclusionesunclassified
See 1 more Smart Citation
“…The literature has also outlined the relationship of ACEs to adolescent and adult behavioral problems among justice-involved populations (Bonta & Andrews, 2016; California Department of Public Health, 2020; Greenfield & Marks, 2010; Horwitz et al, 2001). Studies show that child abuse increases the likelihood of multiple mental health problems (Greenfield & Marks, 2010; Kendall-Tackett, 2000), the earlier use of substances and criminal activity (Grella et al, 2005; Messina & Grella, 2006), repressed anger (Newman & Peterson, 1996; Springer et al, 2007), and violence in adulthood (Horwitz et al, 2001; Kubiak, Fedock, et al, 2017; Saxena & Messina, 2021). In addition, the literature has shown that mental health problems and unresolved issues of trauma and abuse are highly correlated with recidivism (Messina et al, 2004).…”
Section: The Lifelong Impact Of Traumamentioning
confidence: 99%